Computer integrated machine design - Wilson, Charles E. (Prentice Hall, 1997)
This book is designed to take advantage of the almost universal availability of personal computers. Utilizing computer-aided design methods, this book allows readers to optimize a design with a few key strokes; to ask "what if?" ; to examine alternatives; and to plot and interpret the effect of design changes. Emphasis is placed on evaluation and interpretation of results, and development of design skills.